Antibacterial Activity Test Of Epazote Leaf Infusion (Dysphania ambrosioides L.) Against Escherichia coli Bacteria - Carolina, Saroinsong F.; Montolalu, Friska M.; Tumbel, Silvana L.; Kanter, Jabes W.; Maarisit, Wilmar; pakingki, Priska (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2024)
The most common health problem in Indonesia is bacterial infection. Dysphania ambrosioides L., also known as epazote leaves, is an herbal plant that has antimicrobial potential. This research was conducted to see at what concentration there is antibacterial activity of epazote leaf infusion Dysphania ambrosioides L. against Escherichia coli bacteria. This laboratory experimental study used a complete randomized design (RAL) research. Antibacterial activity testing of epazote leaves was carried out using the disc paper diffusion method with concentrations of 50%, 75%, and 100%. Epazote leaves are boiled in an infusion pan for 15 minutes, until the temperature reaches 90 degrees Celsius. Ampicillin positive control 10 ?g/disc. Based on the test results of secondary metabolites of positive epazote leaf infusion there are alkaloids, flavonoids, tannins, saponins, triterpenoids, and phenolics. The results of the study showed that infusion of epazote leaves inhibited Escherichia coli bacteria by diameter inhibition. Average at a concentration of 50% = 14.04 mm, 75% = 16.92 mm, 100% = 17.94 mm, which means that there is antibacterial activity of epazote leaf infusion against Escherichia coli bacteria.